Determinan Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Julia Julia; Haryono Umar (Jurnal Akuntansi dan Governance, 2021)
This study aims to find out the factors that determine the value of the company. The research method used is quantitative method. The population of this research is a manufacturing company listed on the Indonesia Stock Exchange during 2015-2018 with sampling techniques in the form of purposive sampling so that 14 companies were selected as final samples. The data analysis performed is multiple linear regression. The result of this research shows that profitability, age of company and capital structure has a positive effect on firm value while managerial ownership, independent board of commissioner, audit committee, firm size, dividend policy, company productivity and liquidity did not have influence on firm value